MODEL OF DISTRIBUTION OF INFORMATION RESOURCES IN COMPUTER NETWORKS - Zhukov , I. A.; Zaichenko Yu.P., Yu.P.; Pechurin , N. K. (Problems of Informatization and Management, 2005)
A simple mathematical model of the problem of placing information files on the nodes of a computer network with a common bus topology and considerations for its generalization are described. As a criterion for the optimality of the model, the minimum sum of average service times for requests arriving within a unit of time is used. The description of two algorithms for the analysis of the mathematical model is given.